Property toward Husband Doesn't Provide Children and Wife in the Overview of the Compilation of Islamic Law - Suenta Karina Siregar; Utary Maharani Barus; Yezrizawati (Randwick International of Social Science Journal, 2021)
The study was conducted to find out Compilation of Islamic Law governing the distribution of joint property, the application of the principle of partnership and the legal considerations of judges in the Supreme Court Decision of the Republic of Indonesia on Case Number 266K/AG/2010 in terms of the Compilation of Islamic Law against husband doesn’t provide for his children and his wife. This research uses normative juridical research methods that use secondary data consisting of primary, secondary, and tertiary legal materials with descriptive analysis and data collection tools are carried out by library research supported by data obtained through field research at Bantul Religious Courts. The results of this research is known that the regulation regarding the distribution of joint property to husbands who do not provide for their children and wives is not detailed in the Compilation of Islamic Law. This partnership causes the position of husband and wife to be the same in some respects, in other respects to be different, the husband becomes the head of the family, the wife becomes the head in charge of household regulation, each has a role, position, rights, obligations, and responsibilities, all of which complement and perfect each other, every role has rights and every position has obligations, whoever has more obligations or who bears greater obligations, he is the one who has more rights than the others. The judge to resolve the conflict must be able to resolve it objectively based on the applicable law, determine the facts in the trial including the relevant facts and the choice of which legal rules will be used as the basis for resolving the case.